Barriers to Baseline Needs for Early Detection of Breast Cancer among Iraqi Female Patients - alalwan, nada; alattar, wafa; Al Mallah, nawar (Iraqi National Journal of Nursing Specialties, 2016)
Background: Breast Cancer is the most common malignancy among the Iraqi population; the majority of cases are still diagnosed at advanced stages with poor prospects of cure. Early detection through promoting public awareness is one of the promising tools in its control. Objectives: To evaluate the baseline needs for breast cancer awareness in Iraq through exploring level of knowledge, beliefs and behavior towards the disease and highlighting barriers to screening among a sample of Iraqi women complaining of breast cancer. Methodology: Two-hundred samples were enrolled in this study; gathered from the National Cancer Research Center of Baghdad University and the Oncology Teaching Hospital of the Medical City throughout the year 2015. The study population comprised two groups: the first included 100 female patients who were receiving treatment for breast cancer (Group A), while another 100 randomly selected apparently healthy women served as Control (Group B). Those were asked to complete a structured questionnaire which was designed to explore the level of knowledge, beliefs, behavior towards breast cancer and the barriers to early diagnosis. The studied variables included the socio demographic and clinical data, women needs and beliefs regarding breast health and cancer care, and the barriers to screening. Results: Ninety percent of patients with breast cancer in Group I recorded a minimum score of Good; they have answered confidently that the disease is common among women, can be curable when detected at early stages and is not contagious. They also display a significantly higher attitude regarding performing BSE, receiving routine CBE check up and having the courage to be informed about the diagnosis of cancer. Although both groups believe that early detection of cancer should be promoted culturally, Group I displayed a stronger reaction to place this approach as a priority in the community. Overall, both groups do not believe that the disease is usually fatal, could bring disgrace to the family leading to divorce, and did not consider mammography as an embarrassing procedure against religious beliefs. Nevertheless, the majority refuse to be examined by a male doctor and to undergo screening mammography if they have no complaints. Recommendations: Feasible strategies should be more promptly adopted to overcome barriers to early detection of breast cancer among the Iraqi patients; focusing on promoting public health education and ensuring the availability of accessible well equipped diagnostic facilities.